Survival in canine tetanus – retrospective analysis of 42 cases (2006–2020) - Zitzl, Johannes; Dyckers, Jens; Güssow, Arne; Lehmann, Hendrik; Hazuchova, Katarina (Frontiers in Veterinary Science, 2022)
Objective: To define factors associated with survival in dogs with tetanus and to evaluate the prognostic significance of an established severity classification scheme. Methods: Medical records of dogs with the clinical diagnosis of tetanus were retrospectively reviewed with regard to signalment, clinical signs, clinicopathological findings on admission, wound characteristics, complications, therapeutic measures, and survival to discharge. Based on the extracted data, dogs were graded according to a previously published 4-class severity scheme. Non-parametric tests were applied for comparisons between survival categories. Results: Forty-two dogs fulfilled inclusion criteria, of which 32 survived. Of 10 non-survivors, 4 died and 6 were euthanised. Non-survivors were more often younger than 2 years of age (6/10 vs. 7/32 dogs, p=0.023), had shorter duration of specific signs of tetanus (time from onset of typical signs to presentation) (2 vs. 4 days, p=0.016), were prescribed less often antibiotics prior to presentation (p=0.006), had higher tetanus severity grade (10/12 dogs in Class III or IV died, p<0.001), more often received acepromazine (p=0.009) and atropine (p=0.012), and more often had hyperthermia (p=0.005) and respiratory complications (pneumonia, laryngeal spasm; p=0.008). Wound characteristics, the use of tube feeding, metronidazole, methocarbamol, magnesium and antitoxin were not significantly different between non-survivors and survivors. Clinical significance and conclusion: Young dogs with a rapid course of severe disease have guarded prognosis. The previously described severity classification scheme proved valuable in predicting survival. Prospective multi-center studies are needed to clarify the prognostic significance of age, sedative usage and modified versions of an established classification scheme, including the presence of respiratory complications.